HIV-1 transmission within marriage in rural Uganda: a longitudinal study. - Samuel Biraro; Eugene Ruzagira; Anatoli Kamali; James Whitworth; Heiner Grosskurth; Helen A Weiss (PLoS ONE)
Background Early initiation of antiretroviral therapy reduces risk of transmission to the uninfected partner in HIV discordant couples, but there are relatively little observational data on HIV transmission within couples from non-trial settings. The aims of this paper are to estimate HIV incidence among HIV discordant couples using longstanding observational data from a rural Ugandan population and to identify factors associated with HIV transmission within couples, including the role of HSV-2 infection. Methods Using existing data collected at population-wide annual serological and behavioural surveys in a rural district in southwest Uganda between 1989 and 2007, HIV discordant partners were identified. Stored serum samples were tested for HSV-2 serostatus using the Kalon ELISA test. HIV seroconversion rates and factors association with HIV seroconversion were analysed using Poisson regression. Results HIV status of both partners was known in 2465 couples and of these 259 (10.5%) were HIV serodiscordant. At enrollment, HSV-2 prevalence was 87.3% in HIV positive partners and 71.5% in HIV negative partners. Of the 259 discordant couples, 62 converted to HIV (seroconversion rate 7.11/100 PYAR, 95%CI; 5.54, 9.11) with the rate decreasing from 10.89 in 1990-1994 to 4.32 in 2005-2007. Factors independently associated with HIV seroconversion were female sex, non-Muslim religion, greater age difference (man older than woman by more than 15 years), higher viral load in the positive partner and earlier calendar period. HSV-2 was not independently associated with HIV acquisition (HR 1.62, 95%CI; 0.57, 4.55) or transmission (HR 0.61, 95%CI; 0.24, 1.57). No transmissions occurred in the 29 couples where the index partner was on ART during follow up (872 person-years on ART). Discussion HIV negative partners in serodiscordant couples have a high incidence of HIV if the index partner is not on antiretroviral therapy and should be provided with interventions such as couple counselling, condoms and antiretroviral treatment.